Discomfort, Revolt and Abjection in Skim - Downey, Adrian; Whitty, Pam (Journal of the Canadian Association for Curriculum Studies, 2020)
This presentation emerges from our experiences teaching an online, asynchronous children’s literature graduate course. Across its six-year history, teacher-participants have responded variously to the graphic novel Skim. Recently, when confronted with an image in the novel depicting a kiss between a female high school student and her female teacher, some course members focused solely on the kiss, seeming to dismiss the text entirely. To think through this unprecedented occurrence, and to consider its philosophic and curricular constraints/possibilities, we draw on the thinking of Julia Kristeva and those who interpret her work. Specifically, we are thinking about the role of discomfort in leading to Kristeva’s abjection—or, a casting out of the perceived other—and Sonja Arndt’s “dominant need to know” as possibly protecting against dwelling within the uncertain chaos of discomfort and the resulting redefinition of self. This presentation contributes to the ongoing conversation around pedagogies of discomfort. We also consider the distinct temporal experience of reading a graphic novel and suggest that the unique temporality of both the assigned reading and teacher-participants’ lives may encourage/discourage dwelling in discomfort. In closing, we discuss possible curricular and pedagogic shifts we might make to open spaces for dwelling with/in discomfort.